Biomonitoring with the Use of the Herbal Plant Taraxacum officinale as a Source of Information on Environmental Contamination - Respondek, Zuzanna; Isinkaralar, Oznur; Świsłowski, Paweł; Isinkaralar, Kaan; Rajfur, Małgorzata (MDPI AG, 2024)
The aim of this study was to assess the level of contamination of the common dandelion—Taraxacum officinale—with selected metals (Mn, Fe, Ni, Cu, Zn, Cd, and Pb) and to demonstrate that this plant can be used in passive biomonitoring of industrial sites. Two sample transects (the first was near a forest, an area potentially uncontaminated by analytes [A], while the second ran near a steel mill, a contaminated area [B]), each about 1.5 km long, located in Ozimek, Opole Province, Poland, were used in this study. Metals in plant and soil samples were determined by atomic absorption spectroscopy (AAS). Based on the analysis of the obtained results to determine the concentration of metals, plants at site A were more contaminated with Mn (240 mg/kg d.m.) and those at site B with Fe (635 mg/kg d.m.). Mean Pb values (8.39 mg/kg d.m.) were higher at the industrial site (B) and statistically significant at the forest site (A), together with Mn and Fe at the p < 0.001 level. The BCF values for T. officinale showed that Cu (0.473) and Zn (0.785) accumulated to an average degree on both transects. This shows that dandelion is heavily loaded with these metals. Both dandelion and soil samples showed the highest concentrations of Mn, Fe, and Zn, especially in the polluted area B, which is the result of pollution not only from the smelter (dust from electric arc furnaces in steel smelting, extraction installations in production halls transmitting pollutants into the air from molding sand, or waste from molding and core masses dumped on the heap and blown by the wind from the landfill) but also from the high anthropopressure caused by human activity—for example, heating processes or road transport. Our results confirmed that Taraxacum officinale can be successfully used as a herbal plant in passive biomonitoring to assess the quality of the environment, but it must be collected from uncontaminated areas if we want to use it like a medicinal plant.
Keywords: Botany; metals; bioconcentration factor; Article; soil; dandelion; QK1-989; bioindicator; pollution; atomic absorption spectrometry; 15. Life on land; 6. Clean water; 3. Good health; 13. Climate action; 11. Sustainability